Genome-wide identification of the AcMADS-box family and functional validation of AcMADS32 involved in carotenoid biosynthesis in Actinidia - Lin, Zhiyi; He, Zunzhen; Ye, Daoling; Deng, Honghong; Lin, Lijin; Wang, Jin; Lv, Xiulan; Deng, Qunxian; Luo, Xian; Liang, Dong; Xia, Hui (Frontiers in Plant Science, 2023)
MADS-box is a large transcription factor family in plants and plays a crucial role in various plant developmental processes; however, it has not been systematically analyzed in kiwifruit. In the present study, 74 AcMADS genes were identified in the Red5 kiwifruit genome, including 17 type-I and 57 type-II members according to the conserved domains. The AcMADS genes were randomly distributed across 25 chromosomes and were predicted to be mostly located in the nucleus. A total of 33 fragmental duplications were detected in the AcMADS genes, which might be the main force driving the family expansion. Many hormone-associated cis-acting elements were detected in the promoter region. Expression profile analysis showed that AcMADS members had tissue specificity and different responses to dark, low temperature, drought, and salt stress. Two genes in the AG group, AcMADS32 and AcMADS48, had high expression levels during fruit development, and the role of AcMADS32 was further verified by stable overexpression in kiwifruit seedlings. The content of α-carotene and the ratio of zeaxanthin/β-carotene was increased in transgenic kiwifruit seedlings, and the expression level of AcBCH1/2 was significantly increased, suggesting that AcMADS32 plays an important role in regulating carotenoid accumulation. These results have enriched our understanding of the MADS-box gene family and laid a foundation for further research of the functions of its members during kiwifruit development.